Broadband Sensing with Undetected Photons with Strong Parametric Amplification - Hashimoto, Kazuki; Chekhova, Maria V. (2023 Conference on Lasers and Electro-Optics, CLEO 2023, 2023)
We develop an SU(1,1) interferometer with an aperiodically-poled LiNbO3 crystal in the high-parametric-gain regime to demonstrate Fourier-transform spectroscopy and optical coherence tomography with undetected photons.
CRIS-Team Scopus Importer:2023-11-24